2016
DOI: 10.1002/chem.201602043
|View full text |Cite
|
Sign up to set email alerts
|

Helically Assembled Pyrene Arrays on an RNA Duplex That Exhibit Circularly Polarized Luminescence with Excimer Formation

Abstract: Circularly polarized luminescence (CPL) was observed in pyrene zipper arrays helically arranged on an RNA duplex. Hybridization of complementary RNA strands having multiple (two to five) 2'-O-pyrenylmethyl modified nucleosides affords an RNA duplex with normal thermal stability. The pyrene fluorophores are assembled like a zipper in a well-defined helical manner along the axis of RNA duplex, which, upon 350 nm UV illumination, resulted in CPL emission with pyrene excimer formation. CPL (glum ) levels observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…However, the observation of CPL from small organic molecules (SOMs), albeit generally showing smaller dissymmetry factors ( g ), has recently created considerable interest in the dye chemistry community . Potential applications are chiral sensing or the preparation of chiroptical systems with innovative photophysical design . Helicenes belong to the most frequently reported CPL‐SOM architectures, among them carbo[ n ]helicenes, helicenes that incorporate heteroatoms (azahelicenes, oxahelicenes, thiahelicenes), and metallahelicenes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the observation of CPL from small organic molecules (SOMs), albeit generally showing smaller dissymmetry factors ( g ), has recently created considerable interest in the dye chemistry community . Potential applications are chiral sensing or the preparation of chiroptical systems with innovative photophysical design . Helicenes belong to the most frequently reported CPL‐SOM architectures, among them carbo[ n ]helicenes, helicenes that incorporate heteroatoms (azahelicenes, oxahelicenes, thiahelicenes), and metallahelicenes …”
Section: Introductionmentioning
confidence: 99%
“…[30] Potential applications are chiral sensing or the preparation of chiroptical systems with innovative photophysical design. [29,30,[41][42][43][44][45][46] Helicenes belongtothe most frequently reported CPL-SOM architectures, amongt hem carbo[n]helicenes, [33,[47][48][49][50][51] helicenes that incorporate heteroatoms (azahelicenes, [52][53][54][55] oxahelicenes, [34,54] thiahelicenes), [56] and metallahelicenes. [57,58] However,d espite the factt hat several BODIPY-basedc hiral architectures were found to show significant CPL effects, [39,46,[59][60][61][62][63][64] azabora [n]helicenes, that incorporate boron directly in the helical architecture, were reported only in as ingle work so far.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrene fluorophores can be associated like a zipper in a well‐defined helical manner along the RNA duplex, which results in strong excimer fluorescence and circular dichroism signals due to exciton coupling between the pyrenes . Recently, we found that the helical pyrene zipper associations on RNA exhibit circularly polarized luminescence with dissymmetric factors up to +3.5×10 −2 in dilute aqueous solutions …”
Section: Introductionmentioning
confidence: 99%
“…Zipper‐like chromophore‐arrays, in which the chromophores are arranged in an alternating fashion from incorporation into both strands of the duplex, have attracted widespread interest because they can lead to promising properties, such as energy‐ and charge‐transfer between the chromophores after hybridization . While various chromophores have been applied to the construction of zipper‐like arrays, most of them are arranged inside the duplex or in the minor groove of the duplex. In contrast, only a few chromophores have been applied for the construction of zipper‐like arrays in the major groove of the duplex;, thus, the construction of zipper‐like arrays in the major groove remains a challenge.…”
Section: Introductionmentioning
confidence: 99%